[Retracted] The correlation between the femoral artery intima-media thickness and the severity of coronary artery diseases - Viet, Nguyen Quoc; Binh, Ho Anh; Quan, Nguyen Phuoc Bao; Khoa, Phan Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
The article is retracted on the author request